2018
DOI: 10.1111/ijfs.13919
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids, volatile compounds and microbial quality preservation with an oregano nanoemulsion to extend the shelf life of hake (Merluccius hubbsi) burgers

Abstract: Hake (Merluccius hubbsi) is the most important fish of Argentinean industry. The preservative effects of an oregano essential oil (EO) nanoemulsion (NE) on hake burgers (FB) during 15 days at 4°C were studied. Fatty acids determined by gas chromatography coupled with mass spectrometry (CG-MS), volatile compounds determined by solid phase microextraction (SPME) coupled with CG-MS, total volatile basic nitrogen (TVBN), and microbial count was measured. ANOVA and DCG tests were performed. After 14 days, significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…The major compounds were terpinolene (18.62 g/100 g), thymol (16.87 g/100 g), γ-terpinene (15.08 g/100 g), and ortho-cymene (11.08 g/100 g). A similar composition was reported previously ( 5 , 23 , 42 ). This clone was shown to have higher levels of the bioactive phenol thymol than any other OEO from Argentina ( 5 , 43 ).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The major compounds were terpinolene (18.62 g/100 g), thymol (16.87 g/100 g), γ-terpinene (15.08 g/100 g), and ortho-cymene (11.08 g/100 g). A similar composition was reported previously ( 5 , 23 , 42 ). This clone was shown to have higher levels of the bioactive phenol thymol than any other OEO from Argentina ( 5 , 43 ).…”
Section: Resultssupporting
confidence: 90%
“…The antimicrobial or other biological activities of OEOs has been deeply studied; there is a direct correlation between chemical composition and biological properties ( 3 , 5 , 23 ). The antimicrobial effects are related to phenolic compounds, monoterpenes hydrocarbon, total monoterpenes, and sesquiterpenes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amphiphilic structure of phospholipids is responsible for the excellent emulsifying properties of lecithin, and the negative charges of phosphate groups provide repulsive electrostatic interactions important to the stability of emulsion droplets [46,84,85]. Asensio et al developed a preservative NE for hake burgers constituted by a 16% oregano EO stabilized with 3% soy lecithin [86]. Some authors also reported the synergistic emulsifying action of lecithins, in EO-based NEs, in presence of other biopolymers such as Arabic gum and sodium caseinate [87,88].…”
Section: Surfactantmentioning
confidence: 99%
“…Liang et al added MCT to peppermint EOs in the formulation of a stable antimicrobial NE, to prevent the Ostwald ripening phenomenon [78]. The same inhibitor was used by Asensio et al to retard the ripening effect on an oregano EO-bases NE [86]. MCT also proved to be an optimal vehicle to deliver active substances since it was considered able to increase their bioavailability [121].…”
Section: Oil Phasementioning
confidence: 99%